1996
DOI: 10.1093/brain/119.1.309
|View full text |Cite
|
Sign up to set email alerts
|

Abnormalities of the balance between inhibition and excitation in the motor cortex of patients with cortical myoclonus

Abstract: Patients with cortical myoclonus may have purely focal or multifocal jerks, or they may have additional bilateral or generalized jerks, suggesting the spread of excitatory myoclonic activity between the cerebral hemispheres and across the sensorimotor cortex. The factors contributing to this spread of activity were investigated in 10 patients with multifocal cortical myoclonus and eight patients with multifocal and bilateral or generalized cortical myoclonus. The two groups were termed 'non- spreaders' and 'sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
38
1
1

Year Published

1996
1996
2004
2004

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 126 publications
(49 citation statements)
references
References 15 publications
9
38
1
1
Order By: Relevance
“…The reduction in early ICI without changes in ICF in our JME patients provides further evidence to support the hypothesis that inhibitory mechanisms may be altered in JME (19)(20)(21). This finding is in agreement with previous paired TMS investigations on the excitability of motor areas in epilepsy (15)(16)(17). However, in those studies, paired TMS was performed in progressive, severe myoclonic epilepsy (16,17), whereas paired TMS using short ISIs has been investigated only unilaterally in a small number of JME patients (1 5).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The reduction in early ICI without changes in ICF in our JME patients provides further evidence to support the hypothesis that inhibitory mechanisms may be altered in JME (19)(20)(21). This finding is in agreement with previous paired TMS investigations on the excitability of motor areas in epilepsy (15)(16)(17). However, in those studies, paired TMS was performed in progressive, severe myoclonic epilepsy (16,17), whereas paired TMS using short ISIs has been investigated only unilaterally in a small number of JME patients (1 5).…”
Section: Discussionsupporting
confidence: 92%
“…Intraoperative monitoring has shown that the MEP amplitude at long ISIs (100 to 150 milli-seconds) occurs at the cortical level (13). Paired TMS has been used as a research tool to investigate motor cortex excitability in different forms of epilepsy (14)(15)(16)(17) and in several neurological diseases (1 6,lS). Reduced cortical inhibition was observed in progressive myoclonic epilepsy (15,16) and in partial epilepsy (14).…”
mentioning
confidence: 99%
“…Patients with cortical myoclonus [42] of the human motor cortex in epilepsy indicate that it may be possible to characterize the disordered cortex excitability in a given patient on the basis of altered threshold or intracortical excitability. In the future, the technique of noninvasive TMS may facilitate the prediction of optimal AED treatment (ion channel blockers versus neurotransmitter modulators) for a given patient.…”
Section: Relationship To Concepts Of Epileptogenesis and To Previous mentioning
confidence: 99%
“…In our case, both waking and sleep EEGs were normal. However, SSEP were abnormal and consistent, with a decrease in local cortico-cortical inhibition and expression of hyperexcitability of motor cortex 22 . Moreover, the remission of myoclonies in a few months gives additional support to the hypothesis of an idiopathic form.…”
Section: Discussionmentioning
confidence: 92%